2016
DOI: 10.1097/hp.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium-DTPA Model Application with USTUR Case 0269

Abstract: A plutonium-DTPA (Pu-DTPA) biokinetic model was introduced that had originated from the study of a plutonium-contaminated wound. This work evaluated the extension of the Pu-DTPA model to United States Transuranium and Uranium Registry (USTUR) Case 0269 involving an acute inhalation of a plutonium nitrate aerosol. Chelation was administered intermittently for the first 7 mo as Ca-EDTA, mostly through intravenous injection, with Ca-DTPA treatments administered approximately 2.5 y post intake. Urine and fecal bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Nevertheless, the activity level cleared in urine following DTPA administration diminished with therapy progression. This has already been observed in previously reported cases who received a prolonged chelation treatment regimen, regardless of when therapy was started and the radiocompound concerned [Am oxide, early treatment: [15]; Pu nitrate, early treatment [16]; Am oxide, early treatment: [7]; Pu nitrate, delayed treatment [17]; Am nitrate, delayed treatment: [4]; Pu nitrate, delayed DTPA treatment: [5], [6], [18]; Pu nitrate, delayed treatment: [8]].…”
Section: Dtpa-enhanced Elimination Of Plutonium Slowly Diminishes As supporting
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, the activity level cleared in urine following DTPA administration diminished with therapy progression. This has already been observed in previously reported cases who received a prolonged chelation treatment regimen, regardless of when therapy was started and the radiocompound concerned [Am oxide, early treatment: [15]; Pu nitrate, early treatment [16]; Am oxide, early treatment: [7]; Pu nitrate, delayed treatment [17]; Am nitrate, delayed treatment: [4]; Pu nitrate, delayed DTPA treatment: [5], [6], [18]; Pu nitrate, delayed treatment: [8]].…”
Section: Dtpa-enhanced Elimination Of Plutonium Slowly Diminishes As supporting
confidence: 58%
“…Thus, the long-term treatment regimen underwent by the present human case decorporated plutonium material even though it started lately after plutonium internalization. Several previous studies of human cases have already reported an effectiveness of late DTPA therapies begun (or started again) several months or years after plutonium or americium contamination (Am inhalation case : [4]; USTUR Pu inhalation case 0269: [5] and [6]; USTUR Am inhalation case 0846: [7]; USTUR Pu inhalation/wound case 0785: [8]]. In the present case, the late chelation treatments with 1-g DTPA did not appear more e cient than those with 0.5-g DTPA ( Fig.…”
Section: Radiotoxicological Data and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these factors will limit transuranic deposition drastically in systemic target tissues, including the liver. In the present and other contamination cases [americium nitrate, delayed treatment ( Roedler et al 1989 ); plutonium nitrate, delayed DTPA treatment ( James et al 2007 ; Konzen et al 2016 ; Dumit et al 2019a )], individuals internalized moderately soluble forms of plutonium (nitrate) or americium (oxide), and the chelation treatment regimen was initiated belatedly. In these cases, because of the non-negligible fraction of the radiocompound quickly dissolved at the primary site of contamination and absorbed into the bloodstream, the amount of activity deposited in the liver, and hence in hepatocytes, should be sufficient enough to observe a treatment-induced increased fecal activity following DTPA treatment.…”
Section: Resultsmentioning
confidence: 81%
“…Thus, the long-term treatment regimen undergone by the present human case decorporated plutonium material even though it started late after plutonium internalization. Several previous studies of human cases have already reported an effectiveness of late DTPA therapies begun (or started again) several months or years after exposure to plutonium or americium [americium inhalation case ( Roedler et al 1989 ); USTUR plutonium inhalation case 0269 ( James et al 2007 ; Konzen et al 2016 ; Dumit et al 2019a ); USTUR americium inhalation case 0846 ( Breustedt et al 2019 ); and USTUR plutonium inhalation/wound case 0785 ( Dumit et al 2019b )]. In the present case, the late chelation treatments with 1-g DTPA did not appear more efficient than those with 0.5-g DTPA (Fig.…”
Section: Resultsmentioning
confidence: 99%